Stratigraphy and structure of the Peshawar basin, Pakistan - Hussain, Ahmad; Dipietro, Joseph A.; Pogue, Kevin R. (Journal of Nepal Geological Society, 1998)
The Peshawar intermontane basin is a broad, oval shaped and low-lying depression at the southern margin of the Himalaya. It lies to the north of the Attock-Cherat Range and contains rocks transitional between the sedimentary fold-thrust belt to the south and a metamorphic terranc to the north. The basin came into existence as the Kalachitta Range was faulted south on the Main Boundary Thrust (MBT pushing the Siwalik foreland basin still farther south. The basin sediments predominantly comprise of the lacustrine, deltaic and fluvial deposits, which arc overlain by loess, flood plain and alluvial fans of younger age. As a result of the present study, especially the findings of conodonts, the bedrock sequence of the Peshawar basin established previously, has been modified and revised. An almost complete sequence of rocks ranging from the Precambrian to Triassic age has been established for the first time in the Peshawar basin. The study of the Landsat data, aerial photographs and subsequent field studies indicate presence of zone of late Quaternary deformation that extends across the southern margin of the Peshawar basin. Lacustrine, fluvial and alluvial fan deposits, which are dated at 2.8 to 0.6 Ma are tilted, folded and faulted along the four left-stepping pressure ridges that extend for nearly 60 km. Alluvial-fan and fluvial sediments are also folded and faulted in the Ghazi area where the base of the Indus River appears to be displaced by a reverse fault with its northwest side up. Additional minor lineaments and faults occur parallel and oblique to the major fault structures.